Tanggung Jawab Negara Terhadap Pencemaran Laut dari Limbah Buangan PLTU di Kawasan Pesisir Pantai - Muhammad Mutawalli (Program Studi Hukum Keluarga Islam, 2021)
This study aims to determine how the environmental legal arrangements regarding state responsibility for marine pollution from wastewater discharged PLTU (power plant steam) in the coastal area and how the forms of state responsibility for marine pollution from liquid waste discharged PLTU in coastal areas. This type of research is normative legal research using legal material collection techniques through library research methods that are analyzed descriptively qualitatively. The results of this study are by implementing programs made by the government such as in the case of the IPLC program, PROPER, and the government to supervise, monitor, and carry out unannounced visits to companies. As IPLC is a liquid waste disposal permit aimed at business or industrial activities that use water sources as a place to dispose of liquid waste from the results of its business activities. Not only that to prevent and deal with industrial waste, the government must play an active role both through legislation. The government must intensify sustainable development, that is sustainable development with the meaning of development that is forward-looking with a view to being able to be used by present and future generations.Penelitian ini bertujuan untuk mengetahui bagaimana pengaturan hukum lingkungan tentang tanggung jawab negara atas pencemaran laut dari limbah cair buangan PLTU dikawasan pesisir pantai dan bagaimana bentuk-bentuk tanggung jawab negara atas pencemaran laut dari limbah cair buangan PLTU dikawasan pesisir pantai. Jenis penelitian ini adalah penelitian hukum normatif dengan menggunakan teknik pengumpulan bahan hukum melalui metode penelitian pustaka yang dianalisis secara deskriptif kualitatif. Hasil dari penelitian ini yaitu dengan menerapkan program yang dibuat oleh pemerintah seperti dalam hal program IPLC, PROPER, dan melakukan pengawasan, monitoring, maupun melakukan inspeksi mendadak ke perusahaan. IPLC adalah sebuah izin pembuangan limbah cair yang ditujukan pada kegiatan usaha atau industri yang menggunakan sumber-sumber air sebagai tempat pembuangan limbah cair dari hasil kegiatan usahanya. pemerintah harus berperan aktif baik melalui perundang-undangan. Pemerintah harus menggiatkan pembangunan berkonsep sustainable development yaitu pembangunan yang berwawasan ke depan dengan maksud agar mampu dimanfaatkan oleh generasi yang akan datang.